The Role of Mitochondrial Dynamics and Mitophagy in Carcinogenesis, Metastasis and Therapy - Wang, Yigang; Liu, Hui-Hui; Cao, Yu-Ting; Zhang, Lei-Lei; Huang, Fang; Yi, Cong (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are key cellular organelles and play vital roles in energy metabolism, apoptosis regulation and cellular homeostasis. Mitochondrial dynamics refers to the varying balance between mitochondrial fission and mitochondrial fusion that plays an important part in maintaining mitochondrial homeostasis and quality. Mitochondrial malfunction is involved in aging, metabolic disease, neurodegenerative disorders, and cancers. Mitophagy, a selective autophagy of mitochondria, can efficiently degrade, remove and recycle the malfunctioning or damaged mitochondria, and is crucial for quality control. In past decades, numerous studies have identified a series of factors that regulate mitophagy and are also involved in carcinogenesis, cancer cell migration and death. Therefore, it has become critically important to analyze signal pathways that regulate mitophagy to identify potential therapeutic targets. Here, we review recent progresses in mitochondrial dynamics, the mechanisms of mitophagy regulation, and the implications for understanding carcinogenesis, metastasis, treatment, and drug resistance.